FEEDBACK ON A PUBLICLY DISTRIBUTED IMAGE DATABASE: THE MESSIDOR DATABASE - Decencière, Etienne; Zhang, Xiwei; Cazuguel, Guy; Lay, Bruno; Cochener, Béatrice; Trone, Caroline; Gain, Philippe; Ordonez, Richard; Massin, Pascale; Erginay, Ali; Charton, Béatrice; Klein, Jean-Claude (Image Analysis and Stereology, 2014)
The Messidor database, which contains hundreds of eye fundus images, has been publicly distributed since 2008. It was created by the Messidor project in order to evaluate automatic lesion segmentation and diabetic retinopathy grading methods. Designing, producing and maintaining such a database entails significant costs. By publicly sharing it, one hopes to bring a valuable resource to the public research community. However, the real interest and benefit of the research community is not easy to quantify. We analyse here the feedback on the Messidor database, after more than 6 years of diffusion. This analysis should apply to other similar research databases.